FACTORS ASSOCIATED WITH VAGINITIS IN THIRD-TRIMESTER PREGNANT WOMEN AT CA MAU OBSTETRICS AND PEDIATRICS HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with vaginitis during the third trimester of pregnancy.Subjects and Methods: This study involved pregnant women in their third trimester who presented for examination and treatment at Ca Mau Obstetrics and Pediatrics Hospital from June 2024 to July 2025.Results: Statistically significant factors associated with vaginitis in the third trimester (p
Keywords: associated factors, vaginitis, pregnancy.